Proportionality–Progressivity of Biological Assets for Agricultural Prosperity - Enriqueta Mancilla Rendón; Carmen Lozano Arizmendi (Nova Scientia)
The aim of this research is to analyze the application of the principle of proportionality–progressivity to the tax rates established by local Mexican governments on biological assets, assessing their impact on the tax burden regression of small, medium, and large enterprises that carry out economic activities in agriculture. The Suits index was applied to measure the progressivity and regressivity of taxes applied to agribusinesses through a critical hermeneutic analysis of the tax burden by biological assets. The study concludes that most of the taxes on biological assets of the state tax system are progressive, and two of them are highly regressive. This study contributes to the understanding of state tax structures in agriculture, highlighting disparities across Mexico’s 32 state governments. The originality of the study provides the method to measure the progressivity-regressivity of taxes.